Changes in bone turnover induced by aerobic and anaerobic exercise in young males - Woitge, Henning W.; Friedmann-Bette, Birgit; Suttner, Stefan; Farahmand, Iris; Müller, Martin; Schmidt-Gayk, Heinrich; Bärtsch, Peter; Ziegler, Reinhard; Seibel, Markus J. (Journal of bone and mineral research, 1998)
Physical activity is considered an important factor in attaining bone mass. However, the mechanisms by which exercise affects bone metabolism are not completely understood. The present study was performed to investigate the effects of aerobic and anaerobic exercise on bone turnover. Twenty healthy young males (aged 20-29 years) were followed through an 8-week program of aerobic (n = 10) and anaerobic training (n = 10). Ten age-matched individuals served as controls. Serum bone-specific alkaline phosphatase (BAP), serum osteocalcin (OC), and urinary pyridinoline (Pyd) and deoxypyridinoline (Dpd) were determined as indices of bone metabolism. After 4 weeks of aerobic training, serum BAP and OC (p < 0.01), and urinary Pyd (p < 0.001) and Dpd (p < 0.01) were significantly reduced. After 8 weeks, BAP and OC levels had returned to baseline values, whereas the urinary cross-link excretion remained low. In the anaerobic training group, elevated levels of BAP (p < 0.05 vs. week 4), OC (p < 0.05 vs. week 4), and Pyd (p < 0.01 vs. week 0) were observed after 8 weeks of exercise. Changes in urinary Pyd and Dpd (week 0 vs. week 8) were positively correlated with changes in the mean power level in the Wingate test, a parameter of the anaerobic performance capacity (r = 0.50 and r = 0.55, p < 0.01, respectively). In the controls, no significant changes in biochemical markers were observed. We conclude that aerobic and anaerobic training excert different effects on bone metabolism. While aerobic training led to changes compatible with reduced bone resorption activity, anaerobic training seems to result in an overall accelerated bone turnover. Therefore, the impact of physical activity on bone turnover may depend on the kind of exercise performed.
Elektronische Reproduktion der Druck-Ausgabe 4. Dezember 2009
Gesehen am 23.01.2024